Emerging Trend and Causes of Discrepancy between Proposed and Actual Flows of Foreign Capital into Nepalese Energy Sector - Dhungel, Bashu Dev; Lamichhane, Pitambar (International Journal of Energy Economics and Policy, 2024)
This paper aims to investigate the trend and causes of vast gap between actual and proposed FDI flows into energy sector by employing principal component analysis and one sample t test. Foreign direct investment is a main source of capital for the development of energy products in Nepal. Therefore, government of Nepal has emphasized to rise inflows of foreign capital to bridge the gap between demand and supply of capital in energy area. However, Nepal has received very small amount of actual FDI from the proposed FDI. It is found the increasing trend of FDI flows into energy sector after 2014/15 and risk factors of the country, market size, administrators’ quality, availability of physical infrastructure and public servant performance are the major factors causing the all proposed foreign capital do not actually flow into the energy sector. To minimize this divide, it is imperative to enhance country-risk factors. To narrow this gap, it is imperative to enhance country-risk factors and enhance the performance of bureaucrats in their specific domains.